Influence of e-WOM engagement on consumer purchase intention in social commerce. Issue 4 (1st June 2018) - Yusuf, Ali Sahabi; Che Hussin, Ab Razak; Busalim, Abdelsalam H.
Abstract : Purpose: As a business paradigm, social commerce (s-commerce) has brought about a new stage of innovation, and by extension, has transmuted the power from seller to buyer. S-commerce is a combination a commercial and social activities in which individuals may spread word of mouth (WOM) about their shopping experiences and knowledge and provide information about product and services to their to their friends. This kind of social interactions among individuals has increased the potentials of eWOM communication. Given such a backdrop, this paper aims to look into the influence of eWOM engagement on consumers' purchase intention in s-commerce, which may complement the current effort of the research community in this area. Design/methodology/approach: This study used elaboration likelihood model, theory of reasoned action and social support theory to investigate the influence of eWOM engagement on consumers' purchase intention in s-commerce. The study used 218 respondents to evaluate the proposed model using SmartPLS. Findings: The empirical results indicate that information characteristics, consumer behavior and technological factors exert a positive influence on consumer purchase intentions. All hypotheses between attitude toward eWOM, information credibility, innovativeness, website quality and eWOM engagement are significant. Also, eWOM engagement has a significant positive influence on consumer purchase intention. However, information quality and social support does not have any significant relationship with eWOM engagement. Research limitations/implications: This study seeks to address the dearth of research in the field of s-commerce, especially as it relates to eWOM. The study proposes a new model and empirically validates the hypothesized relationships. This research can serve as a stepping stone for future research in this field. Practical implications: This study is one of the early studies focusing on the influence of eWOM engagement, especially in s-commerce. The study offers comprehensive and empirically validated factors pertaining to eWOM engagement in s-commerce. The results of this study are also important to practitioners and online companies' managers. The study's model has demonstrated the contextualization of what makes customers engage in eWOM and its influence in s-commerce. The study will also offer insights for firms on how to encourage eWOM engagement among customers. Originality/value: A new eWOM engagement model in s-commerce is proposed with consideration on information characteristics, consumer behavior, technological and social factors. The model is validated afterwards.